2022
DOI: 10.3389/fsurg.2022.819335
|View full text |Cite
|
Sign up to set email alerts
|

The N6-Methyladenosine Modification and Its Role in mRNA Metabolism and Gastrointestinal Tract Disease

Abstract: The N6-methyladenosine (m6A) modification is the most abundant internal modification of messenger RNA (mRNA) in higher eukaryotes. Under the actions of methyltransferase, demethylase and methyl-binding protein, m6A resulting from RNA methylation becomes dynamic and reversible, similar to that from DNA methylation, and this effect allows the generated mRNA to participate in metabolism processes, such as splicing, transport, translation, and degradation. The most common tumors are those found in the gastrointest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…Recently, m6A modi cation of RNAs has been considered as a new layer of epigenetic regulation. This physiological process is shown to play crucial roles in modulation of cell differentiation, proliferation, and self-renewal by controlling RNA stability, translation, and splicing [31][32][33]. Previous studies have found that m6A is mainly involved in the modi cation of mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, m6A modi cation of RNAs has been considered as a new layer of epigenetic regulation. This physiological process is shown to play crucial roles in modulation of cell differentiation, proliferation, and self-renewal by controlling RNA stability, translation, and splicing [31][32][33]. Previous studies have found that m6A is mainly involved in the modi cation of mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…YTHDC2 high levels accelerated protein translation of metastasis-related genes (HIF-1α) and promote distant metastasis in colorectal cancer. 36 Besides, YTHDC2 could also induce susceptibility to pancreatic and hepatocellular carcinoma. 37 , 38 However, due to the existence of histological differences, YTHDC2 has conflicting roles in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence that m6A may also enhance translation [5]. The impact of these modifications depends on multiple factors, including the presence of specific m6A reader proteins and the location of m6A on the mRNA [5,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%